Hydrothermal incubation-induced amyloid fibrillation of wheat gluten peptide: regulation of functional properties via multi-scale structural and morphological evolution - Yuwen Wang; Mengyuan Li; Zheng Wang; Lingfang Zhang; Binghua Sun; Sen Ma (Food Hydrocolloids, 2027)

Elucidating the mechanism of wheat bran arabinoxylan on the freeze-thaw stability of gluten protein: From the perspectives of spatial conformation and molecular polymerization of gluten protein and micro-morphology of gluten network - Mengyuan Li; Lingfang Zhang; Yuwen Wang; Xichen Lin; Xinhao Li; Li Li; Sen Ma (Food Hydrocolloids, 2026)

The role of wheat endogenous starch granule size in reducing oil absorption of instant fried noodles - Shuzhen Yang; Lingfang Zhang; Xue Wu; Xiaoxi Wang; Binghua Sun (Food Chemistry, 2026)

Supply-demand and income-integrated perspectives of healthcare accessibility in high-density, transit-oriented cities - Zijin Zhou; Esther H.K. Yung; Shuai Yuan; Lingfang Shao; Xiqian Zhang (Transportation Research Part D: Transport and Environment, 2026)

Unveiling the impact of mixed-strain solid-state fermentation on wheat bran dietary fiber: gluten protein structure evolution, dough rheological modulation and steamed bread quality enhancement - Xinhao Li; Rui Huang; Mengyuan Li; Lingfang Zhang; Xiaojie Qian; Binghua Sun; Sen Ma; Li Li (Food Hydrocolloids, 2026)

No-tillage shapes a Sinorhizobium-centered rhizosphere network in saline-alkali soybean fields - Zhe Chen; Chuang Ma; Zhiqiang Hu; Zongling He; Jianchao Zhang; Shuyu Li; Lingfang Zhu; Xihui Shen; Baowei Bai (Plant and Soil, 2026)

Performance and mechanism of phosphorus transformation in the microalgal-bacteria symbiotic system under varying light intensities - Xinyi Huang; Yingxin Chen; Jingxian Che; Xinyi Zhang; Lingfang Huang; Ting Ran; Beibei Wu; Yun Zhou (Bioresource Technology, 2026)

VALD-3 Induces GSDME-Dependent Pyroptosis via ROS/JNK/Bax Pathway in Triple-Negative Breast Cancer Cells - Xuhui Zhao; Xuhong Pan; Weijie Ma; Shuang Liang; Dezhuan Da; Jiawei Liu; LingFang Zhang; Pengfei Song; Hongling Li (Biochemical Genetics, 2026)

Silica-induced telomere dysfunction promotes pulmonary fibrosis through the activation of the cGAS-STING pathway - Qiuqian Qian; Simiao Pan; Xiaodong Li; Xiaoxue Gong; Zhaoqiang Jiang; Xing Zhang; Jianlin Lou; Lingfang Feng (Toxicology, 2026)

CardioNVT: an AI platform for immunostaining-free, high-throughput cardiomyocyte ploidy assessment in situ - Zehao Yao; Lina Bai; Zhongkai Luo; Yuan Liu; Lingfang Chen; Minjiong Zhao; Youzhi Sun; Libo Zhang; Yu Nie (Science Bulletin, 2026)

The influence of fulvic acid on molybdenum bioavailability assessed by Caenorhabditis elegans - Qian Huang; Lingfang Cui; Zhixin Song; Ming Li; Chao Zhang; Wenzhong Tang; Jianyin Huang (Journal of Environmental Management, 2026)

Corrigendum to “Non-monotonic effect of starch content on protein digestion in wheat noodles mediated by protein network structural changes” [Food Res. Int. 228 (2026) 118418] - Lingfang Zhang; Shuzhen Yang; Xiaojie Qian; Mengyuan Li; Sen Ma; Binghua Sun; Xiaoxi Wang (Food Research International, 2026)

Non-monotonic effect of starch content on protein digestion in wheat noodles mediated by protein network structural changes - Lingfang Zhang; Shuzhen Yang; Xiaojie Qian; Mengyuan Li; Sen Ma; Binghua Sun; Xiaoxi Wang (Food Research International, 2026)

Chitosan oligosaccharide enhances the tolerance of Pinus koraiensis to Bursaphelenchus xylophilus through the flavonoid biosynthesis pathway - Jiawei Zhang; Lingfang Ye; Bin Wang; Qiaoli Chen; Xiaohang Hu (Pesticide Biochemistry and Physiology, 2026)

Moderate wheat starch content reduces oil absorption and in vitro starch digestibility of instant fried noodles - Shuzhen Yang; Lingfang Zhang; Xue Wu; Xiaoxi Wang; Binghua Sun (Food Research International, 2026)

Microbial abundance shapes latitudinal pattern of the greenhouse gas production potential in blue carbon ecosystems - Lingfang Ni; Chuancheng Fu; Gang Li; Kai Feng; Ye Deng; Jiaping Wu; Carlos M. Duarte; Yuan Li; Dongdong Zhang (Water Research, 2025)

A new method of consistency evaluation of brain drugs: a case study of edaravone - Liqiang Gu; Yanping Hu; Yinfang Lai; Sheng Zhang; Haoran Wang; Xiaozhen Xu; Lingfang Chen; Yuhua Shi; Jiechao Chen; Xiaochun Sun; Yuan Zhang; Lingzhi Hu (Regulatory Toxicology and Pharmacology, 2025)

Efficient biosorption of molybdenum (VI) using Chlorella pyrenoidosa biomass: Mechanistic insights and sustainable application in water remediation - Zhixin Song; Lingfang Cui; Xunan Li; Zichen Zhang; Chao Zhang; Gangfu Song; Yu Zhao; Wenzhong Tang (Journal of Cleaner Production, 2025)

Benzothiadiazole induces Pinus koraiensis to resist pine wilt disease - Jiawei Zhang; Hanqi Jia; Lingfang Ye; Qiaoli Chen; Xiaohang Hu (Pesticide Biochemistry and Physiology, 2025)

Designing food matrix structure by adjusting the ratio of soluble/insoluble wheat bran dietary fiber to mitigate the inhibition on wheat protein digestion: Application in noodles - Lingfang Zhang; Qianyi Jiang; Binghua Sun; Xiaoxi Wang; Sen Ma (Food Chemistry, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Dynamic changes of stomatal distribution, protein structural and liquor properties of oat dough during the fermentation process affected by moderately gelatinized oat flour - Xiaojie Qian; Lingfang Zhang; Binghua Sun; Sen Ma; Chong Liu; Xiaoxi Wang (Food Research International, 2025)

Seasonal dynamics of microbial communities link to summer-autumn aquaculture disease outbreaks in Sanggou Bay - Longfei Lu; Lingfang Ni; Chunxiang Ai; Dongdong Zhang; Pengfei Zheng; Xuejing Li; Xin Liu; Hongyue Dang (Frontiers in Marine Science, 2025)
Marine microorganisms play a vital role in aquaculture by influencing water quality and the health of cultured species. Relative to conventional mono-species aquaculture, integrated multi-trophic aquaculture is more environmentally friendly and economically sustainable. However, the temporospatial dynamics of the microbial community in different aquaculture modes and their roles in the seasonal diseases of aquacultural organisms are largely unknown. Here, the seawater bacterial communities and potential pathogens were investigated over thirteen months in three different aquaculture types in Sanggou Bay, a typical maricultural area with nearly 60 years of history. Seasonality played a primary role, while aquaculture type played a subtle role in shaping the bacterioplankton community. Diverse potential pathogens were identified, and r -strategist bacteria, most of which were opportunistic pathogens and typified by Vibrio species, increased and dominated in late summer and autumn, a period of high-risk disease outbreaks in mariculture organisms. Network analyses indicated that the increase in r -strategist bacteria reduced the complexity of microbial interactions, and Vibrio halioticoli (OTU1389), a hub species with extensive positive correlations to other Vibrio OTUs, likely contributed to the increase of pathogenic vibrios due to its macroalgae degradation capability. The major potential pathogenic Vibrio OTUs were further corroborated by genome analyses and environmental simulation experiments using pathogenic Vibrio isolates, including two new species. Moreover, we found seawater dissolved oxygen, temperature, and transparency correlated significantly with the bacterioplankton temporospatial dynamics and the seasonal outbreaks of bacterial pathogens. Our results emphasize the necessity of synchronically monitoring the bacterial community, its pathogens-stimulating species, such as V. halioticoli and other macroalgae-degrading bacteria, and critical physicochemical parameters for predicting and preventing pathogen outbreaks in mariculture.

Assessing the use of GPM DPR and IMERG products for Typhoon Mujigae over the southern coastal provinces of China - Xue Li; Lingfang Chen; Yangbo Chen; Ruihao Zhang; Zhihua Zhu; Hui Yin; Baolin Jiang (Atmospheric Research, 2025)

An exploration on the structural characteristics and antioxidant activities of casein hydrolysates fermented by Lactiplantibacillus plantarum A56 and A157 - Cuicui Duan; Lingfang Zhang; Cheng Wu; Yi Zhang; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Binding properties of olfactory proteins to host volatiles, free fatty acids and cuticular hydrocarbons in the termite Reticulitermes aculabialis - Wenxu Yang; Chenxu Ye; Lu Wang; Jinjuan Nie; Xinyi Liu; Tiange Zhang; Wenxiu Zhang; Noor us Saba; Lingfang Yin; Lianxi Xing; Xiaohong Su (Insect Biochemistry and Molecular Biology, 2025)

Stand age-related effects of mangrove on archaeal methanogenesis in sediments: Community assembly and co-occurrence patterns - Lingfang Ni; Jiaping Wu; Hongyue Dang; Carlos M. Duarte; Kai Feng; Ye Deng; Daoqiong Zheng; Dongdong Zhang (Science of The Total Environment, 2024)

Integrated DNA methylation analysis of peripheral blood from asbestos exposed populations and patients with malignant mesothelioma reveals novel methylation driver genes of diagnostic and prognostic relevance - Lingfang Feng; Tao Li; Biao Xu; Jing Huang; Hailing Xia; Zhaoqiang Jiang; Junfei Chen; Simiao Pan; Xing Zhang; Hua Jiang; Jianlin Lou (Environmental Pollution, 2024)

Protein digestibility in wheat noodles: The inhibitory effect and its mechanism of wheat bran dietary fiber - Lingfang Zhang; Xiaojie Qian; Binghua Sun; Shuzhen Yang; Xiaoxi Wang; Sen Ma (Journal of Cereal Science, 2024)

Development of a new synchronous fluorescence spectrometry combined with Al3+ sensitized for simultaneous and rapid determination of trace flumequine, ciprofloxacin and doxycycline hydrochloride residues in wastewater - Xiaodan Zheng; Menglin Wang; Shiqi Zhang; Zhima Yangcuo; Lifang He; Lingfang Xie; Yurou Ye; Guifen Xu; Zhonghui Chen; Qihong Cai (Water Research, 2024)

Colonization characteristics and dynamic transition of archaea communities on polyethylene and polypropylene microplastics in the sediments of mangrove ecosystems - Qiong Wang; Gang Zheng; Lingfang Ni; Heng Wang; Weiye Li; Peng Guo; Yi Wang; Daoqiong Zheng; Jiaping Wu; Dongdong Zhang (Journal of Hazardous Materials, 2024)

Characterization of a novel endornavirus isolated from the phytopathogenic fungus Rhizoctonia solani - Yangyi Li; Xingxue Huang; Guolin Zhou; Anhua Ye; Yaohua Deng; Lingfang Shi; Runhua Zhang (Archives of Virology, 2024)

Improved simultaneous nitrification–denitrification in fixed-bed baffled bioreactors treating mariculture wastewater: Performance and microbial community behaviors - Peng Guo; Qiong Wang; Lingfang Ni; Silong Xu; Daoqiong Zheng; Yi Wang; Fang Cai; Mingyu Cui; Zhiwei Zheng; Xiuqing Gao; Dongdong Zhang (Bioresource Technology, 2023)

Higher ecological risks and lower bioremediation potentials identified for emerging OPEs than legacy PCBs in the Beibu Gulf, China - Li Zhang; Lingfang Ni; Heng Wang; Zhichao Zhang; Yichun Wu; Renming Jia; Junyu He; Zuhao Zhu; Haiyan Jin; Xing Ren; Dongdong Zhang (Environmental Research, 2023)

Photo-aging promotes the inhibitory effect of polystyrene microplastics on microbial reductive dechlorination of a polychlorinated biphenyl mixture (Aroclor 1260) - Youhua Chen; Lingfang Ni; Qing Liu; Zhaochao Deng; Jiawei Ding; Li Zhang; Chunfang Zhang; Zhongjun Ma; Dongdong Zhang (Journal of Hazardous Materials, 2023)

Bias adjustment of satellite rainfall data through Gaussian process regression (GPR) based on rain intensity classification in the Greater Bay Area, China - Xue Li; Yangbo Chen; Yueyuan Zhang; Lingfang Chen (Theoretical and Applied Climatology, 2023)

Developing a framework for urban flood modeling in Data-poor regions - Shichao Xu; Yangbo Chen; Yueyuan Zhang; Lingfang Chen; Huaizhang Sun; Jun Liu (Journal of Hydrology, 2023)

Isolation and evaluation of strong endogenous promoters for the heterologous expression of proteins in Pichia pastoris - Yafei Zhang; Shengyan Wang; Lingfang Lu; Chenshan Zhang; Fan Cai; Yao Lin; Yide Huang (World Journal of Microbiology and Biotechnology, 2022)

Altered brain activity in the bilateral frontal cortices and neural correlation with cognitive impairment in schizophrenia - Lingfang Yu; Lei Guo; Xinyu Fang; Fuyin Yang; Yan Chen; Yewei Wang; Dandan Wang; Zenan Wu; Ruimei Liu; Xing Tian; Chen Zhang (Brain Imaging and Behavior, 2022)

Evaluating the effect of midpalatal corticotomy-assisted rapid maxillary expansion on the upper airway in young adults using computational fluid dynamics - Juan Li; Lingfang Shi; Xiayao Zhang; Luxi Weng; Hong Chen; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2021)

Heat contribution of the Indonesian throughflow to the Indian Ocean - Tiecheng Zhang; Weiqiang Wang; Qiang Xie; Lingfang Chen (Acta Oceanologica Sinica, 2019)

The genome sequence of Brassica campestris chrysovirus 1, a novel putative plant-infecting tripartite chrysovirus - Jun Zhang; Zhonghao Zhao; Rong Hu; Lingfang Guo; Limin Zheng; Zhenguo Du; Zujian Wu; Shouguo Fang; Songbai Zhang; Yong Liu (Archives of Virology, 2017)

Complete sequence of a double-stranded RNA from the phytopathogenic fungus Erysiphe cichoracearum that might represent a novel endornavirus - Zhenguo Du; Wenzhong Lin; Ping Qiu; Xiaojuan Liu; Lingfang Guo; Kangcheng Wu; Songbai Zhang; Zujian Wu (Archives of Virology, 2016)

Identification and molecular characterization of Panax notoginseng virus A, which may represent an undescribed novel species of the genus Totivirus, family Totiviridae - Lingfang Guo; Xin Yang; Wei Wu; Guanlin Tan; Shouguo Fang; Songbai Zhang; Fan Li (Archives of Virology, 2016)

Sphingobium endophyticus sp. nov., isolated from the root of Hylomecon japonica - Lingfang Zhu; Kaiyun Xin; Chaoqiong Chen; Changfu Li; Meiru Si; Liang Zhao; Xu Shi; Lei Zhang; Xihui Shen (Antonie van Leeuwenhoek, 2015)

Rhizobium smilacinae sp. nov., an endophytic bacterium isolated from the leaf of Smilacina japonica - Lei Zhang; Xu Shi; Meiru Si; Changfu Li; Lingfang Zhu; Liang Zhao; Xihui Shen; Yao Wang (Antonie van Leeuwenhoek, 2014)

Solirubrobacter taibaiensis sp. nov., isolated from a stem of Phytolacca acinosa Roxb. - Lei Zhang; Lingfang Zhu; Meiru Si; Changfu Li; Liang Zhao; Yahong Wei; Xihui Shen (Antonie van Leeuwenhoek, 2014)

Pseudoxanthomonas gei sp. nov., a novel endophytic bacterium isolated from the stem of Geum aleppicum - Lei Zhang; Linfang Wei; Lingfang Zhu; Changfu Li; Yao Wang; Xihui Shen (Antonie van Leeuwenhoek, 2014)

Isolation of RNA of high quality and yield from Ginkgo biloba leaves - Tao Wang; Nianhui Zhang; Lingfang Du (Biotechnology Letters, 2005)